Analisis Tingkat Kebisingan Rona Lingkungan Awal Pembangunan Jalan Alternatif : (Studi kasus Jalan Matabondu Lalingato Kabupaten Kolaka Timur, Sulawesi Tenggara) - Fauzi, Amirul; Sumarlin, Sumarlin; Assiddieq, Moch. (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2024)
This research study focus on noise level characteristics at 4 (four) points and the magnitude as early life environment for alternative road construction plan of Matabondu-Lalingato in East Kolaka Regency. Noise is unwanted sound from activity in level and certain time which can cause disturbance human health and environmental comfort. Research methods use Sound Level Meter (SLM) and Geographic Positioning System (GPS). Results shows that the noise level at first point is 48.60 dB, at second point is 49.60 dB, at third point is 46.80 dB, at fourth point is 50.30 dB, average is 48.82 dB. Conclusion noise level at point 1, 2, 3, and 4 meet the standards by environmental ministry